Perceptions of 2022 Library and Information Science Students on the Use of Artificial Intelligence (AI) in Completing Academic Assignments - Putri, Azzahra Fermi; Nurizzati, Nurizzati (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The rapid development of Artificial Intelligence (AI) in higher education has transformed how students access, manage, and use academic information. The use of AI in completing academic assignments has increased substantially because it is perceived to offer efficiency, convenience, and speed in learning activities. However, the increasing adoption of AI also raises concerns regarding technological dependency, information validity, and academic ethics. This study aims to analyze the perceptions of 2022 cohort students in the Library and Information Science Program at Universitas Negeri Padang regarding the use of AI in completing academic assignments. A quantitative approach with a descriptive research design was employed. The population consisted of 78 active students from the 2022 cohort, all of whom were selected as respondents using saturated sampling. Data were collected through a four-point Likert-scale questionnaire developed based on the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, covering performance expectancy, effort expectancy, social influence, and facilitating conditions. The data were analyzed using descriptive statistics with the assistance of SPSS version 26.0. The findings reveal that students’ perceptions of AI utilization were categorized as very good, with an achievement level of 90.44%. Among the indicators, facilitating conditions obtained the highest average score of 3.74, followed by effort expectancy and social influence, each with a score of 3.67, while performance expectancy obtained a score of 3.58. These findings indicate that AI is perceived as capable of enhancing effectiveness, efficiency, productivity, and convenience in completing academic assignments. Social environments and technological infrastructure also support students’ adoption of AI technologies. The study concludes that AI has become an important component of students’ academic activities; however, its use must be accompanied by strong digital literacy, critical thinking skills, and academic ethical awareness to ensure responsible and meaningful utilization. These findings provide practical implications for higher education institutions in formulating ethical AI policies and strengthening technology-based learning systems.